Rehabilitasi Psikososial pada Pasien yang mengalami Reaksi Stres Akut di Era COVID-19 - Era Catur Prasetya; Muhammad Afif (Universitas Muhammadiyah Surabaya, 2023)
AbstractAcute Stress Reaction is a strong emotional or physical reaction felt after a sad event. Generally this reaction will subside as part of the body's recovery process. The Covid-19 pandemic period in addition to affecting the physical also affects a person's psychology. After experiencing Covid-19 infection, patients can also experience trauma from it. The incidence of Acute Stress Reaction in COVID-19 patients in the general population is quite high, around 7% to 53%. Reactions to Acute Stress Reaction will be different for each family member, namely changes in behavior, difficulty concentrating, anxiety, fear, sadness or even physical symptoms, headaches, nausea, insomnia. Even though we don't experience it, we must be aware of it. Because the reaction is different as a family is often not aware of the changes to it. If this reaction occurs, it is necessary for the family to provide communication support and regular rest and regular monitoring. If there is no improvement or the reaction is strong enough then you can seek help from a mental health professional.Keywords: Acute Stress Reaction, Covid-19, psychosocial